2021
DOI: 10.1007/s10067-021-05853-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of effectiveness, persistence, and usage patterns of monotherapy and combination therapy tofacitinib in treatment of rheumatoid arthritis in Australia

Abstract: Objective This study aimed to describe the real-world effectiveness and treatment persistence among patients with rheumatoid arthritis treated with monotherapy and combination therapy tofacitinib and biologic disease-modifying antirheumatic drugs (bDMARDs). Methods This was a post hoc analysis of a retrospective, non-interventional study that extracted data for patients treated with tofacitinib or bDMARDs from the Australian OPAL dataset between March 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…We then showed that none of the potential predictors of therapy discontinuation considered, including patient age, previous treatment with biologics, concomitant use of csDMARD, and positivity for RF and/or ACPA, were statistically significant after regression analysis. Similar data were reported by Bilgin et al [ 33 ], Movahedi et al [ 34 ], Bird et al [ 35 ], and Finckh et al [ 36 ], who found no relevant predicting factor for TOFA discontinuation. Our results are also in agreement with a recently published paper analyzing data from a Korean registry, in which no predictive factors for discontinuation of therapy were found, except RF and ACPA positivity, both of which were associated with higher drug retention rates [ 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…We then showed that none of the potential predictors of therapy discontinuation considered, including patient age, previous treatment with biologics, concomitant use of csDMARD, and positivity for RF and/or ACPA, were statistically significant after regression analysis. Similar data were reported by Bilgin et al [ 33 ], Movahedi et al [ 34 ], Bird et al [ 35 ], and Finckh et al [ 36 ], who found no relevant predicting factor for TOFA discontinuation. Our results are also in agreement with a recently published paper analyzing data from a Korean registry, in which no predictive factors for discontinuation of therapy were found, except RF and ACPA positivity, both of which were associated with higher drug retention rates [ 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, both studies included higher proportions of treatment‐refractory (i.e., bDMARD‐experienced) patients than CANTORAL. Conversely, a study of the Australian OPAL real‐world data set, with a comparable proportion of bDMARD‐naive patients to CANTORAL, reported higher month 6 CDAI‐defined LDA and remission rates than in the current analysis ( 11 , 12 ). However, OPAL included a higher proportion of patients in remission at tofacitinib initiation, and patients had a lower median disease duration versus CANTORAL, which may explain these differences.…”
Section: Discussioncontrasting
confidence: 83%
“…Overall, effectiveness and persistence in patients receiving tofacitinib with versus without csDMARDs were similar across real-world studies (12,13,18). In the tofacitinib global clinical trial program, a phase IIIb/IV study showed numeric efficacy differences favoring tofacitinib combination therapy versus monotherapy (34), while persistence with tofacitinib combination and monotherapy were comparable in long-term extension studies (30).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Data from the Rheumatic Diseases Portuguese Register showed that 23% and 40% of patients achieved remission and LDA, respectively, after 6 months of treatment with TNF inhibitors [ 12 ], which is generally in line with our findings. However, in a post hoc analysis of an Australian non-interventional cohort study of patients with RA treated with bDMARDs (abatacept, adalimumab, anakinra, certolizumab pegol, etanercept, golimumab, infliximab, rituximab, and tocilizumab), rates of remission were higher than those observed here: nearly 60% of patients achieved remission at 3 months, which increased to 64% after 18 months [ 13 ]. In contrast, in an analysis of data from the British Society for Rheumatology Biologics Registry for Rheumatoid Arthritis, only 10% of patients treated with infliximab, etanercept, or adalimumab achieved remission at 6 months [ 14 ].…”
Section: Discussionmentioning
confidence: 87%